Alud de datos - Bernal, Isabel (Anuario ThinkEPI, 2015)
Reseña del informe: Mossink,Wilma;Â Bijsterbosch, Magchiel;Â Nortier, Joeri (2013). European landscape study of research data management. Utrecht: SURF. http://goo.gl/CJNlTX